Serum and Adipose Tissue mRNA Levels of ATF3 and FNDC5/Irisin in Colorectal Cancer Patients With or Without Obesity - Zhu, Huijuan; Liu, Meijuan; Zhang, Nianrong; Pan, Hui; Lin, Guole; Li, Naishi; Wang, Linjie; Yang, Hongbo; Yan, Kemin; Gong, Fengying (Frontiers in Physiology, 2018)
Objectives: To explore the ATF3 and FNDC5/irisin protein levels in serum and mRNA levels in subcutaneous and visceral white adipose tissue (sWAT and vWAT) in normal-weight (NW) and overweight/obese (OW/OB) patients with colorectal cancer (CRC). Methods: 76 CRC patients and 40 healthy controls were recruited. Serum ATF3 and irisin levels were detected by ELISA, and the mRNA expression levels in sWAT and vWAT were measured by RT-qPCR. Results: The serum ATF3 levels were 37.2% increased, whereas the irisin levels were 23.3% reduced in NW+CRC patients compared with those in healthy controls. CRC was independently associated with both ATF3 and irisin levels. The probability of CRC was 22.3-fold increased in individuals with high ATF3 levels compared with those with low ATF3 levels, whereas the risk of CRC in subjects with high irisin levels was 78.0% reduced compared to the risk in those with low irisin levels after adjustment for age, sex, BMI and other biochemical parameters. Serum ATF3 and irisin could differentiate CRC patients from controls with receiver-operating characteristic (ROC) curve areas of 0.745 (95% CI, 0.655-0.823) and 0.656 (95% CI, 0.561-0.743), respectively. The combination of ATF3 and irisin exhibited improved diagnosis value accuracy with ROC curve areas of 0.796 (95% CI, 0.710-0.866) as well as 72.6% sensitivity and 80.0% specificity. Conclusions: Increased ATF3 and reduced irisin levels are observed in sera from CRC patients. Individuals with high ATF3 and low irisin levels were more likely to have CRC. ATF3 and irisin represent potential diagnostic biomarkers for CRC patients.